Design and order : perceptual experience of built form - principles in the planning and making of place - Lewis, Nigel C. (John Wiley & Sons, Inc., 2020)
"This book outlines the fundamental characteristics that are evident in the creation of built form and illustrates how they determine the experience of resultant places. It consolidates the key criteria that need to be taken into consideration in the development of built form or urban spaces. While not a design manual for architects, it does provide a coherent overview of the principles that underpin design, and by consideration and illustration of each of the individual elements, an integrated understanding of both the principles and the perception of design is developed. The designer can then apply or discard these principles in the development of urban designs, with a solid understanding the implications of the decisions they make"- Resumé vydavatele